Outcomes of Local versus Free Flaps for Lower Extremity Trauma. Issue 10 (October 2022) - Kondra, Katelyn; Roohani, Idean; Swerdlow, Mark; Brown, Michael; O'Brien, Devon; Pekcan, Asli; Stanton, Eloise; Carey, Joseph
Background: Lower extremity reconstruction often requires soft tissue transfer for limb salvage. Flaps are allocated based on injury size, location, and shape coupled with surgeon expertise. Ideally, vascularized tissue should have similar outcomes across local and free tissue transfers. By evaluating outcomes from a Level 1 trauma center, we aim to provide recommendations regarding surgical management of leg reconstruction with respect to local versus free flap implementation. Methods: This retrospective review evaluated patient medical history, demographics, flap characteristics, and outcomes from LAC + USC between 2007-2021 using an internal database. Outcomes included failure rates, complications, and ambulation. Results: 357 lower extremity flaps were placed on 322 patients; 187 (52.4%) were local and 170 (47.6.%) were free flaps. Twenty-one (11.2%) local flaps suffered significantly more postoperative hardware infections and/or osteomyelitis compared to nine (5.3%) free flaps. Eleven (5.9%) local flaps developed partial necrosis, four requiring revision; 12 (6.4%) total local flaps required revision. Comparatively, sixteen (9.4%) free flaps developed partial necrosis, seven requiring revision; 18 (10.6%) total free flaps required revision. Flap survival was 96.3% for local versus 93.5% for free flaps. Percentage of fully ambulatory patients and time to final ambulation was not significant across cohorts. Discussion: Local flaps may portent higher risk for infection; though the cause is not clear, the results may be confounded by comorbidities. Nevertheless, there were no significant differences in flap survival or number of fully ambulatory patients across cohorts. Future studies should evaluate aesthetic results and patient satisfaction across flap types.